(untitled) (Fiep Bulletin - online, 2014)
In accordance with Penteado (1999), the Television and the school are two social agencies that have in the knowledge its raw material. The first one is clearly organized, according to an industrial model of production, from which it spreads out and it produces knowledge; the second, is organized in accordance with a bureaucratic model of rendering of services, it is conceived as a channel of transmission and diffusion of knowledge, in its procedures identified as a pedagogy conservative and traditional. Knowing-if that the television is inside of the school, through the viewer who frequents it, and restored in so definitive way that can be considered a universal standard of our culture, the objective of the present study consisted of evaluating the transmission of the culture of mass for the television, beyond the preference for activities of the traditional culture or culture of mass of twenty and eight students of the systems conventional and integral, of 2ª and 4ª series of a private, situated school in the south zone of Belo Horizonte, Minas Gerais. A composed quantitative questionnaire for three dimensions was applied: the first dimension was composed for demographic data of the pupil; the second dimension evaluated the preference of the students in relation to the televising programming and the third dimension searched esteem the preference of the students as the activities of the traditional culture or mass culture. All the participants had been informed of the study objectives and that they could leave to participate at any time besides having signed term of assent free and clarified to participate of the study. For statistical treatment, descriptive analysis of the data was used and analysis of reply frequency using itself the statistical package Microsoft Excel will be Windows. The results had show that great exposition of the students to the mass culture exists, however they had demonstrated to greater interest for activities of the traditional culture.